INVESTIGATION OF SECONDARY SCHOOL STUDENTS’ ATTITUDES TOWARDS SCIENCE COURSE ACCORDING TO SOME VARIABLES - 1 - Halil İbrahim YILDIRIM (Fırat University, 2019)
This study was conducted to investigate into attitudes towards science course levels of 5th, 6th, 7th and 8th grade students from secondary school; to determine the correlation between attitudes and academic success; to investigate into influence of variables of gender, class level, success at science course, mother education, father education, mother working situation, family income level, liking science course and course attendance level, frequency of experiment–activity on attitude level towards science course so as to draw a suggestion for improving attitudes level in this course. A survey model is used in the research. It employs cross-sectional survey model. The research was conducted on 1780 students from the twelve public secondary schools in Ankara City along the second term in the academic year of 2015-2016. “The Attitudes towards Science Course Scale” was used as data collection tool. Independent Samples t-Test, One-Way ANOVA, Pearson Correlation Coefficient were used to analyze for the data. As a result of the study, it was determined that gender, mother education, father education, mother working situation and family income level variables were not statistically significant on attitude levels. A positive, statistically significant and high correlation was determined between the motivation and success. Furthermore, it was concluded that frequency of experiment–activity, liking science course and course attendance level variables were statistically significant on attitude level. In addition it was concluded that attitude decreases from 5th to 8th grade significantly.